Analyzing Online Twitter Discussion for Male Infertility via the Hashtag #MaleInfertility. Issue 1 (January 2020) - Balasubramanian, Adithya; Yu, Justin; Thirumavalavan, Nannan; Lipshultz, Larry I.; Hotaling, James M.; Pastuszak, Alexander W.
Abstract: Introduction: We characterized Twitter discussions focused on male infertility using #Male Infertility, the official Urology Ontology hashtag for the condition. Methods: Symplur, a Twitter analytics service, was used to analyze activity, users and tweet content for #MaleInfertility between August 2015 and November 2018. Activity was quantified by monthly tweets and yearly cumulative users. Users were classified based on geography, occupation and organizational affiliation. Content analysis was undertaken by analyzing retweets, links, media, mentions, replies, frequently used words and hashtags. Results: A total of 11, 325 tweets and 3, 241 users using #MaleInfertility were identified. Most tweets (73%) were sent with links. The average ± SD number of #MaleInfertility tweets per month increased from 152 ± 47 in 2015 to 439 ± 2, 013 in 2018 (p <0.001). The number of users increased from 95 to 3, 241 during this period. Linear regression revealed that the #MaleInfertility discussion increased by 8.7 tweets per month and 80 users per month across the study period (p <0.0001). Users tweeted from 22 countries and doctors comprised 39% of the top 100 influencers. Popular associated hashtags included #Infertility, #IVF and #Sperm. Tweet content codification revealed that tweets were mainly focused on providing online patient support. Conclusions: Twitter discussions focused on male infertility are increasing in volume. Our analysis highlights that doctors and organizations associated with health care are the primary influencers of #MaleInfertility Twitter discussions. This increase in users and tweet volume highlights that Twitter is an emerging digital tool to disseminate information about male infertility online.